Revitalizing Islamic Education in Shaping the Religious Character of the Digital Generation at Muhammadiyah 5 Junior High School in Surakarta - Amrul Fahmi; Muhammad Wildan Shohib (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The development of digital technology has had a significant impact on the formation of students' religious character. The digital generation faces challenges in the form of high exposure to digital media, shifting moral values, and weakening consistency in religious practices. This study aims to analyze the factors that cause Islamic Religious Education (IRE) learning to be less than optimal in shaping the religious character of students and to describe efforts to revitalize IRE learning that is relevant in the digital age. The research uses a descriptive qualitative approach with a case study design at Muhammadiyah 5 Junior High School in Surakarta. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that the suboptimal learning of Islamic Education is influenced by external factors such as the digital environment and differences in family backgrounds, as well as internal factors such as limited learning time and the dominance of theoretical learning methods. The challenges of the digital generation also create a gap between the technological skills and moral maturity of students. However, Islamic education schools and teachers have made revitalization efforts through the integration of Islamic values into school culture, religious habits, strengthening religious programs, and utilizing digital technology in learning. The revitalization of Islamic education learning that emphasizes a balance between cognitive, affective, and religious practice aspects has proven to be relevant in strengthening the religious character of students in the digital age.